Menstrual tampons and vaginal pessaries: regulation of intravaginal medical devices by the US FDA - Pollard, Colin M. (Frontiers in Reproductive Health, 2023)
Catamenial products like menstrual tampons for managing menses and vaginal pessaries for managing urinary incontinence and uterine prolapse are products that can be inserted and removed from the vagina repeatedly over a woman's lifetime. In the United States (US), these products are considered to be medical devices and are regulated by the Center for Devices & Radiological Health (CDRH) of the Food and Drug Administration (FDA). As such, they are subject to both premarket and postmarket regulatory controls. Both tampons and pessaries have a long history of safe and effective use, and FDA applies a risk-based approach to both premarket entry as well as continued postmarket regulatory controls. Practicing clinicians are often the initial source of ideas for medical device improvements. This article is intended to help such clinicians to understand the regulatory challenges faced by development teams who seek to introduce these kinds of products to the US market. It explains FDA's risk-based classification of medical devices and the 510(k) premarket notification as the primary regulatory mechanism for market entry. It also highlights key FDA guidance documents and encourages early engagement with FDA when appropriate.